Die-casting aluminum alloy suitable for surface anodic oxidation and preparation method of die-casting aluminum alloy
The composition and process of Al-Si alloy are improved through surface anodization treatment, and the problems of insufficient alloy strength and corrosion resistance are solved, and high-performance and low-cost aluminum alloy production is achieved, which is suitable for high-demand applications.
Patent Information
- Application Number
- CN202510211812.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-25
AI Technical Summary
The existing Al-Si alloys are widely used in the field of die casting, but their strength is low and their corrosion resistance is insufficient, resulting in a lack of theoretical guidance and practical experience in practical applications to effectively improve their corrosion resistance and extend their service life.
The Al-Si-Mn-Mg-Zn-Fe-La-Cu-Os-Ca-Tb-Re alloy that adopts surface anodization treatment improves the strength, wear resistance and corrosion resistance of the alloy by adjusting the alloy composition and process flow.
It realizes the reduction of aluminum alloy production costs and simplification of production processes while maintaining high performance, improves the strength, wear and corrosion resistance of the alloy, and is suitable for making high-demand parts such as mobile phone shells.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material surface treatment, and in particular to a die-casting aluminum alloy suitable for surface anodizing and a preparation method thereof. Background Art
[0002] Al-Si alloy is widely used in automobile, motorcycle, electronics, communication and aerospace industries due to its good die-casting performance, low thermal expansion coefficient and excellent casting performance. In the aluminum alloy series, Al-Si alloy has become the preferred material in the die-casting process with its excellent fluidity, good filling capacity and low shrinkage. This enables Al-Si alloy to meet the production needs of parts with complex shapes, and greatly improves production efficiency while ensuring the accuracy of parts. Among them, in the fields of automobiles and communication equipment, Al-Si alloy occupies an important position due to its lightweight, good thermal conductivity and electromagnetic shielding performance. At present, the Al-Si alloys used for die-casting production mainly include ADC12, A356, A380, A390 and YL112. These alloys meet the needs of die-casting parts in different fields with their good die-casting performance, high mechanical properties and machinability.
[0003] However, Al-Si alloys also have some shortcomings, such as relatively low strength, generally less than 300MPa, and due to the presence of silicon, its corrosion resistance is lower than that of other aluminum alloys. Although Al-Si alloys are widely used in the field of die-casting, there are relatively few studies on the corrosion of die-cast aluminum parts in China. At present, the research on the corrosion influencing factors and mechanism analysis of conventional die-casting Al-Si alloy materials is not in-depth enough. This leads to a lack of systematic theoretical guidance and practical experience in practical applications on how to effectively improve the corrosion resistance of Al-Si alloys and extend the service life of die-castings. Therefore, future research on Al-Si alloys should pay more attention to their corrosion properties, and deeply explore the factors affecting corrosion and their mechanisms, so as to provide a scientific basis for the improvement of alloys and the development of new alloys. At the same time, it is also necessary to strengthen the research between die-casting technology and alloy properties to further optimize the production process of die-castings and improve their comprehensive performance and service life. Summary of the invention
[0004] The object of the present invention is to overcome at least one disadvantage of the prior art and to provide a die-cast aluminum alloy suitable for surface anodization and a preparation method thereof.
[0005] The technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides an aluminum alloy suitable for surface anodizing die-casting, wherein the composition of the alloy is, by mass percentage, Si 2.33-2.60%, Mn 0.4-0.6%, Mg 0.3-0.45%, Zn 0.1-0.5%, Fe 0.2-0.4%, Cu 0.05-0.15%, and the remainder is Al and unavoidable impurity elements.
[0007] In some examples, 0.1-0.3% Os is further added to the alloy by mass percentage.
[0008] In some examples, 0.1-0.3% Ca is further added to the alloy by mass percentage.
[0009] In some examples, Tb 0.2-0.4% by mass is further added to the alloy.
[0010] In some examples, Re is further added to the alloy in an amount of 0.1-0.3% by mass.
[0011] In some examples, the Zn content in the alloy is 0.10-0.15% by mass.
[0012] In some examples, the ratio of Mg:Zn in the alloy is (2.9-3.1):1 by mass percentage.
[0013] In a second aspect, the method for preparing the aluminum alloy provided in the first aspect of the present invention comprises the following steps:
[0014] 1) Weigh the raw materials according to the alloy composition and melt them into aluminum alloy liquid at a melting temperature of 710℃~740℃, remove the slag and stir evenly;
[0015] 2) Refining in an inert gas environment at 710℃~740℃, stirring for 5~20min, keeping warm for 20~30min, removing slag and filtering, and die-casting into aluminum alloy plate ingots;
[0016] 3) Pre-treatment of the aluminum alloy plate ingot by cleaning, pickling, soaking, and electrochemical polishing;
[0017] 4) subjecting the pretreated aluminum alloy plate ingot to an electric anodizing treatment for 30 to 40 minutes;
[0018] 5) Place the aluminum alloy workpiece after the primary electric anodizing treatment in a chemical etching solution and etch at a temperature of 45 to 50°C for 50 to 55 minutes;
[0019] 6) The aluminum alloy workpiece after chemical etching is subjected to secondary electric anodizing treatment for 25 to 30 minutes;
[0020] 7) Immerse the aluminum alloy workpiece in an organic acid solution at room temperature for 50 to 60 minutes for hole opening treatment, then clean it, and then immerse it in a sealing glue for 5 to 10 minutes. Take it out and cure it at room temperature for 5 to 10 minutes. Finally, cure the sample at 100 to 110°C for 2 to 3 hours.
[0021] In some examples, the chemical etching solution in step 5) comprises the following composition: 0.5-1 wt.% phosphoric acid solution, 1.8-2 wt.% chromic acid solution and 1.5-4 wt.% lanthanum nitrate solution.
[0022] In some examples, the etching temperature in step 5) is 45-50° C. and / or the etching time is 50-55 min.
[0023] In some examples, the anodizing treatment conditions of step 4) and step 6) are: placing in a 0.29-0.31 M oxalic acid solution, setting the voltage to 39.5-40.5 V, and operating at a constant temperature of 0-5°C.
[0024] In some examples, the organic acid in step 7) comprises the following composition: 10-12 wt.% malic acid and 15-17 wt.% sorbic acid.
[0025] In some examples, the curing treatment in step 7) includes pre-curing at no more than 40° C. for 5 to 10 minutes, and then fully curing at 100 to 110° C.
[0026] The beneficial effects of the present invention are:
[0027] The present invention aims to reduce the production cost of aluminum alloy and simplify the production process while maintaining high performance, and invents a surface-treated anodized Al-Si-Mn-Mg-Zn-Fe-La-Cu-Os-Ca-Tb-Re alloy. The alloy has high strength, excellent wear resistance and corrosion resistance, and a simple process flow, and can be used to make mobile phone shells, meeting the requirements for alloy wear resistance and corrosion resistance.
[0028] In some embodiments of the present invention, rare earth elements are added to improve the strength and corrosion resistance of the matrix. A very small part of the Tb element is dissolved in α-Al, while most of it is distributed at the grain boundary or combined with elements such as Fe, Si, and Mg to form a second phase. These second phases play a strengthening role in the alloy. At the same time, the Tb element is highly active and can promote the repair of the surface passivation film after pitting nucleation. When the generation rate of the corrosion product film layer exceeds its dissolution rate, the corrosion rate of the alloy will continue to decrease. In addition, the addition of Tb can also improve the microstructure of the alloy, making the arrangement of the primary α-Al solid solution more uniform and regular, and the number of second phases increases and is distributed in a continuous network at the grain boundary, reducing the coarse and harmful AlFeSi phase at the grain boundary, thereby reducing the unevenness of the microstructure and performance, enhancing the continuity of the surface passivation film, and then improving the thermal conductivity, mechanical properties and corrosion resistance of the alloy. Tb combines with Fe in the melt to form intermetallic compounds, which changes the morphology of the AlFeSi phase, reduces the randomly distributed needle-shaped and rod-shaped phases at the grain boundary, and further improves the performance of the alloy.
[0029] In some embodiments of the present invention, the addition of Ca element reduces the porosity of the oxide film and the hardness of the oxide film. Strontium element may promote the oxidation reaction of aluminum in the anodized film of aluminum alloy to form a harder oxide film. The hardness of the strontium-doped oxide film is usually higher than that of the conventional oxide film, thereby improving the wear resistance of the aluminum alloy surface, especially for applications with high strength and high wear resistance requirements. At the same time, strontium can improve the porosity structure of the anodized film, reduce the porosity of the film, and thus improve the overall quality of the oxide film. Oxide films with lower porosity usually have better protective properties and reduce the adsorption of pollutants and corrosive substances by the oxide film.
[0030] In some embodiments of the present invention, precious metals are added to increase the matrix potential and enhance the corrosion resistance of the alloy. After the two rare metal elements Os (osmium) and Re (rhenium) are added to the Al (aluminum) matrix, their overall potential level can be significantly improved. The principle is that they may exist in the form of solid solution, compound or second phase, changing the electrode potential of the Al matrix. At the same time, these two elements can optimize the electrochemical properties of the Al matrix by slowing down the corrosion kinetics, especially reducing the rate of intergranular corrosion. This is because the presence of high-potential elements makes the Al matrix more difficult to corrode in an electrochemical environment, and may slow down the corrosion process by affecting the kinetic parameters of the corrosion reaction, such as reducing the corrosion current density or increasing the corrosion potential. In addition, they may also affect the electrochemical behavior at the grain boundaries, reduce the formation of micro-galvanic cells at the grain boundaries, and thus reduce the tendency of intergranular corrosion.
[0031] In some embodiments of the present invention, the formation of a La-rich coating hinders the cathode-anode reaction and improves the corrosion resistance. During the anodizing pretreatment, lanthanum nitrate is added to form a La-rich coating on the cathode phase to improve the corrosion resistance of the aluminum alloy. The key role of the La-rich coating is that it can effectively hinder the current transfer between the anode and the cathode, reducing the flow of electrons required for the corrosion reaction, thereby slowing down the charge transfer step in the electrochemical corrosion process. Due to the obstruction of current transfer, the corrosion rate of the alloy is significantly reduced.
[0032] In some embodiments of the present invention, the secondary oxidation process regenerates a layer of fine and dense oxide film to improve corrosion resistance. This newly generated oxide film has a higher density and better structure, which can effectively block the invasion of external corrosive media, thereby improving the corrosion resistance of aluminum alloys. At the same time, the increased oxide film thickness also provides an additional physical barrier, further enhancing the corrosion resistance of the material. At the same time, due to the newly generated fine oxidation pores and the denser oxide film structure, the oxide film is tougher and more wear-resistant. Therefore, when subjected to external friction or wear, the oxide film can better protect the base material and extend the service life of the aluminum alloy.
[0033] In some embodiments of the present invention, organic acids in the pore opening treatment help to obtain more ideal pore opening effects and environmentally friendly effects. When sorbic acid and malic acid are used as anodizing pore opening agents, the oxide film that may be formed on the surface of the aluminum alloy is tighter and more uniform than the film treated with other acids, which improves the adhesion of the film. In particular, the oxide film after sorbic acid treatment is smoother, which helps to improve corrosion resistance. Moreover, sorbic acid and malic acid are organic acids with lower toxicity, and their environmental pollution risk is lower than that of phosphoric acid. In particular, sorbic acid, as a natural organic acid, is widely present in fruits and has lower harm to the environment and human body. DETAILED DESCRIPTION
[0034] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.
[0035] The present invention is described in detail below in conjunction with examples, comparative examples and experimental data, but is not intended to identify the key or decisive elements of the present invention or to limit the scope of protection.
[0036] The technical solution of the present invention is further described below with reference to examples. In order to obtain a product with more stable quality, the impurities in each example are controlled to be below 0.25%.
[0037] Example 1
[0038] According to the weight percentage of the constituent elements, Si 2.5%, Mn 0.6%, Mg 0.45%, Fe 0.2%, Zn 0.15%, Cu0.1%, Os 0.3%, Re (rhenium) 0.2%, and the balance is Al. The specific alloy preparation process is as follows:
[0039] 1) Step 1: Weigh the raw materials of the intermediate alloys according to the alloy composition, and according to the designed aluminum alloy composition and mass percentage, put the high-purity aluminum, Al-10Si, Al-20Cu, Al-10Mg, Al-10Zn, Al-10Fe, Al-10Mn, Al-10Os, and Al-10Re intermediate alloys into a melting furnace to melt into aluminum alloy liquid at a melting temperature of 710°C to 740°C, remove the slag and stir evenly;
[0040] 2) Step 2: Use argon with a purity of 99.99% as a carrier gas at 710℃~740℃ and a refining agent that accounts for 0.2% of the weight of the aluminum alloy liquid for refining, stir for 5~20min, and keep warm for 20~30min, remove slag and filter. Bubble a mixed gas consisting of argon with a purity of 99.99% and chlorine with a purity of 99.99% into the aluminum alloy liquid for 15min to remove hydrogen, and the volume percentage of chlorine in the mixed gas is 10%;
[0041] 3) Step 3: Take the alloy ingot prepared in step 2), keep it warm for 10 minutes, pour it into the die-casting storage cylinder with a feeding spoon for die-casting, the pouring temperature is 700-720°C, the mold temperature is 180-200°C, the injection pressure is 85Mpa, the injection time is 3s, the cooling time is 2s, the mold retention time is 10s, and die-cast into an aluminum alloy plate ingot;
[0042] 4) Step 4: Anodizing pretreatment. At room temperature, the aluminum alloy workpiece was placed in acetone, ethanol and deionized water for 40KHz ultrasonic cleaning for 3 minutes respectively. The cleaned aluminum alloy workpiece was immersed in 10% dilute sulfuric acid for 10 minutes. The aluminum alloy workpiece was electrochemically polished at a constant voltage of 15V for 5 minutes in a mixed solution of perchloric acid and anhydrous ethanol at a temperature of 0°C and a volume ratio of 1:4;
[0043] 5) Step 5: Primary electric anodization, placing the pretreated aluminum alloy workpiece in a 0.3M oxalic acid solution, setting the voltage to 40V, and performing anodization treatment for 30min at a constant temperature of 0-5°C;
[0044] 6) Step 6: Chemical etching, placing the aluminum alloy workpiece after the primary electric anodizing treatment in a chemical etching solution, etching at a temperature of 45° C. for 50 minutes, the chemical etching solution comprising the following composition: 0.5-1wt.% phosphoric acid solution, 1.8-2wt.% chromic acid solution and 1.5-4wt.% lanthanum nitrate solution;
[0045] 7) Step 7: Secondary electrical anodizing treatment. The aluminum alloy workpiece after chemical etching is placed in a 0.3M oxalic acid solution again, the voltage is set to 40V, and anodizing treatment is performed at a constant temperature of 0-5℃ for 30 minutes;
[0046] 8) Step 8: Phosphoric acid opening, the aluminum alloy workpiece after the second step of anodizing is immersed in a non-stirring organic acid solution at room temperature for 60 minutes, wherein the organic acid is composed of the following solution: 10-12 wt.% malic acid and 15-17 wt.% sorbic acid;
[0047] 9) Step 9: Ultrasonic clean the sample in deionized water for 4 min and dry at room temperature;
[0048] 10) Step 10: Sealing treatment. The aluminum alloy workpiece after the hole treatment is immediately immersed in the sealing glue. The immersion cycle includes immersing the sample in the sol for 5 minutes, then taking it out at a rate of 80 mm / min, and curing it at room temperature for 10 minutes. Repeat this immersion-curing cycle three times and cure the sample at 110°C for 2 hours.
[0049] Example 2
[0050] According to the weight percentage of the constituent elements, Si 2.5%, Mn 0.6%, Mg 0.45%, Fe 0.2%, Zn 0.15%, Cu 0.1%, Ca 0.3%, Tb 0.3%, and the balance is Al. The specific alloy preparation process is the same as that in Example 1.
[0051] Example 3
[0052] According to the weight percentage of the constituent elements, Si 2.5%, Mn 0.6%, Mg 0.45%, Fe 0.2%, Zn 0.15%, Cu 0.1%, Os 0.3%, Re 0.2%, Ca 0.3%, Tb 0.3%, and the balance is Al. The specific alloy preparation process is the same as that in Example 1.
[0053] Comparative Example 1
[0054] According to the weight percentage of the constituent elements, Si 2.5%, Mn 0.6%, Mg 0.45%, Fe 0.2%, Zn 0.15%, Cu 0.1%, Tb 0.05%, Os 0.4%, Ca 0.05%, Re 0.4%, and the balance is Al. The specific alloy preparation process is the same as that in Example 1.
[0055] Comparative Example 2
[0056] According to the weight percentage of the constituent elements, Si 2.5%, Mn 0.6%, Mg 0.45%, Fe 0.2%, Zn 0.15%, Cu0.1%, Os 0.3%, Re 0.2%, Ca 0.3%, Tb 0.3%, and the balance is Al. In the specific alloy preparation process, the acid used for the pore opening treatment is 5wt% phosphoric acid solution, and the rest of the process is the same as Example 1.
[0057] Comparison of Alloy Properties
[0058] The aluminum alloy plates obtained in the embodiment and the comparative example were tested for corrosion resistance and fluidity, respectively, wherein the corrosion resistance test method was formulated in accordance with GB / T 10125-2021 "Artificial atmosphere corrosion test salt spray test". The test conditions are as follows: the temperature of the salt spray test chamber is 35±2°C, the temperature of the air saturator is 45°C, the humidity is 100%, the test solution is (50±5) g / L NaCl aqueous solution, the water is deionized water, and the test time is 480h. The fluidity is characterized by casting a spiral specimen and measuring its flow length. The test results of the corrosion resistance and fluidity of each embodiment are shown in Table 1.
[0059] Table 1 Test results of mechanical properties, corrosion resistance and fluidity of various examples
[0060] serial number Tensile strength / MPa Corrosion depth / μm Spiral specimen length / mm Example 1 449 97.6 231.9 Example 2 463 95.8 212.6 Example 3 479 81.4 219.4 Comparative Example 1 445 108.6 164.6 Comparative Example 2 451 100.2 178.6
[0061] By comparing Example 1 and Example 3, it can be seen that adding an appropriate amount of Os and Re (rhenium) increases the potential of the aluminum matrix and improves the corrosion resistance of the alloy.
[0062] By comparing Example 2 and Example 3, it can be seen that adding appropriate amounts of Tb and Ca mainly refines the grain size and improves the strength of the alloy.
[0063] By comparing Example 3 with Comparative Example 1, it can be seen that excessive or low amounts of modifying elements are not conducive to improving alloy properties.
[0064] By comparing Example 3 with Comparative Example 2, it can be seen that the use of organic acid can improve the corrosion resistance of aluminum alloy.
[0065] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A die-casting aluminum alloy suitable for surface anodization, characterized in that: In terms of mass percentage, the composition of the alloy is: Si 2.33~2.60%, Mn 0.4~0.6%, Mg 0.3~0.45%, Zn 0.1~0.5%, Fe 0.2~0.4%, Cu0.05~0.15%, and the balance is Al and unavoidable impurity elements.
2. The surface anodized die-casting aluminum alloy according to claim 1, characterized in that: In terms of mass percentage, at least one of the following elements is added to the alloy: Os 0.1~0.3%; Ca 0.1~0.3%; Tb 0.2~0.4%; Re 0.1~0.3%.
3. The surface anodized die-casting aluminum alloy according to claim 1, characterized in that: In terms of mass percentage, the Zn content in the alloy is 0.10-0.15%.
4. The surface anodized die-casting aluminum alloy according to claim 1, characterized in that: In terms of mass percentage, the ratio of Mg:Zn in the alloy is (2.9-3.1):
1.
5. The method for preparing the surface anodized die-casting aluminum alloy according to claim 1, characterized in that: The following steps are involved: 1) Weigh the raw materials according to the alloy composition and melt them into aluminum alloy liquid at a melting temperature of 710℃~740℃, remove the slag and stir evenly; 2) Refining in an inert gas environment at 710℃~740℃, stirring for 5~20min, keeping warm for 20~30min, removing slag and filtering, and die-casting into aluminum alloy plate ingots; 3) Pre-treatment of the aluminum alloy plate ingot by cleaning, pickling, soaking, and electrochemical polishing; 4) subjecting the pretreated aluminum alloy plate ingot to an electric anodizing treatment for 30 to 40 minutes; 5) placing the aluminum alloy workpiece after the primary electric anodizing treatment in a chemical etching solution for etching; 6) The aluminum alloy workpiece after chemical etching is subjected to secondary electric anodizing treatment for 25 to 30 minutes; 7) Immerse the aluminum alloy workpiece in an organic acid solution at room temperature for 50 to 60 minutes to perform hole opening treatment, then clean it, and then immerse it in a sealing glue for 5 to 10 minutes, and take it out to solidify.
6. The preparation method according to claim 5, characterized in that: The chemical etching solution in step 5) comprises the following composition: 0.5-1 wt.% phosphoric acid, 1.8-2 wt.% chromic acid and 1.5-4 wt.% lanthanum nitrate.
7. The preparation method according to claim 5, characterized in that: In step 5), the etching temperature is 45-50° C. and / or the etching time is 50-55 min.
8. The preparation method according to claim 5, characterized in that: The anodizing treatment conditions of step 4) and step 6) are as follows: placing in a 0.29-0.31 M oxalic acid solution, setting the voltage to 39.5-40.5 V, and operating at a constant temperature of 0-5° C.
9. The preparation method according to claim 5, characterized in that: The organic acid in step 7) comprises the following composition: 10-12 wt.% malic acid and 15-17 wt.% sorbic acid.
10. The preparation method according to claim 5, characterized in that: The curing treatment in step 7) includes pre-curing at a temperature not exceeding 40° C. for 5 to 10 minutes and then fully curing at 100 to 110° C.